The tribunal atmosphere: On qualitative barriers to access to justice. Issue 119 (February 2021) - Gill, Nick; Allsopp, Jennifer; Burridge, Andrew; Fisher, Daniel; Griffiths, Melanie; Paszkiewicz, Natalia; Rotter, Rebecca
Highlights: Atmosphere in tribunals is a key factor in access to justice. Cultural geographies of atmosphere can be usefully applied to practical legal processes. Ethnography of asylum hearings provides unique insight into tribunal dynamics. Atmospheres of disorientation, distrust and disrespect threaten access to justice in tribunals. Abstract: Vulnerable groups' direct experiences and impressions of British courts and tribunals have often been overlooked by politicians and policy makers (JUSTICE, 2019). This paper takes a geographical, empirical approach to access to justice to respond to these concerns, paying attention to the atmosphere of First Tier Immigration and Asylum Tribunal hearings to explore the qualitative aspects of (in)access to justice during asylum appeals. It draws on 41 interviews with former appellants and 390 observations of hearings in the First tier immigration and asylum tribunal to unpack the lived experiences of tribunal users and to identify three ways in which the atmosphere in tribunals can constitute a barrier to access to justice. First, asylum appellants are frequently profoundly disorientated upon arrival at the tribunal. Second, appellants become distrustful of the courtroom when they cannot see it as independent of the state. Third they often experience the courtroom procedures and the interactions that take place as disrespectful, inhibiting their participation. These insights demonstrate how the concept of 'atmosphere' can illuminate legal debates in valuable ways. Additionally we argue that legal policy making must find better ways to take vulnerable litigants' experiences into account.